Analisis Dampak Total Harmonic Distortion Terhadap Losses Dan Derating Pada Transformator Distribusi Di Fakultas Teknik Universitas Riau - Robby Dhavitra; Firdaus Firdaus; Feranita Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of the aspects that can affect reduced the quality of electricity is the incidence of harmonics on electric waves due to by non linear loads, causing additional losses and led to decrease in work capacity (derating) the distribution transformer. Results of measurement of harmonics in distribution transformers in Riau University engineering faculty for one week, at certain times indicate the value percentage of 12.57% TDD exceeding the IEEE 519-1992 standard is 5%. This proves that the transformer impaired harmonic currents. As for the voltage distortion does not have problems (not exceeding standards). Based on the measurement results of 18.57% current THD cause losses of 19.3 kW and has a value of 27.4% THDF thus decreasing the capacity of power (kVA) installed or derating of 72.6%.Keywords : Harmonics, Total Harmonic Distortion and Derating